Multiple Routes to Subfunctionalization and Gene Duplicate Specialization - Proulx, Stephen R. (Genetics Society of America, 2012)
Gene duplication is arguably the most significant source of new functional genetic material. A better understanding of the processes that lead to the stable incorporation of gene duplications into the genome is important both because it relates to interspecific differences in genome composition and because it can shed light on why some classes of gene are more prone to duplication than others. Typically, models of gene duplication consider the periods before duplication, during the spread and fixation of a new duplicate, and following duplication as distinct phases without a common underlying selective environment. I consider a scenario where a gene that is initially expressed in multiple contexts can undergo mutations that alter its expression profile or its functional coding sequence. The selective regime that acts on the functional output of the allele copies carried by an individual is constant. If there is a potential selective benefit to having different coding sequences expressed in each context, then, regardless of the constraints on functional variation at the single-locus gene, the waiting time until a gene duplication is incorporated goes down as population size increases.